Design of guyed electrical transmission structures (ASCE, 1997)
Prepared by the Subcommittee on Guyed Transmission Structures of the Committee on Electrical Transmission Structures of the Structural Engineering Institute of ASCE. Design of Guyed Electrical Transmission Structures describes the engineering considerations involved in designing guyed structures to support electric transmission lines. Guyed structures generally have the advantages of being lightweight, easy to erection, capable of preassembly, and requiring a simple foundation design. A considerable range of applications is available, from simple guyed wood poles to the very large guyed steel-latticed structures. This Manual describes various types of guyed structures in use; presents typical guys and fittings; illustrates guy anchors and foundations; explores analysis and design techniques specific to guyed structures; discusses unique construction and maintenance problems; and displays both hand and computer calculations to illustrate some of the concepts discussed in the document.
Keywords: Electric lines -- Poles and towers -- Design and construction.; Guy anchors.; elektronické knihy; electronic books